The Impact of an Outdoor and Adventure Sports Course on the Wellbeing of Recovering UK Military Personnel: An Exploratory Study - Mariana Kaiseler; Chris Kay; Jim McKenna (MDPI AG, 2019)
UK military personnel have faced increased demands over the last three decades; these have affected their wellbeing and caused multiple physical and mental health problems. Currently, bespoke rehabilitation systems may recommend participation in sports programmes. Although research attention has been drawn to the short-term positive effects of these programmes, their long-term impact on psychological wellbeing is unknown. To address this gap, the current study explored the long-term impact of a sports programme on UK military personnel’s ability to make changes in their day-to-day life through the lens of psychological wellbeing. For this purpose, UK military personnel (n = 97) completed an online survey aiming to provide a quantitative and qualitative picture of their experiences of an outdoor and adventure sports programme, underpinned by the basic psychological needs theory, six months following completion. Findings suggest that 75% of respondents found that the course was useful for facilitating adaptive changes. Content analysis suggests that elements of the course seem to satisfy their basic psychological needs of competence, relatedness and autonomy. Activities initiated six months after the course are mostly aligned with improved psychological wellbeing. Useful theoretical and applied implications are discussed.